2016
DOI: 10.1097/md.0000000000004699
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane compared with fentanyl-midazolam-based anesthesia in patients undergoing heart transplantation

Abstract: Inhalation anesthetics provide myocardial protection for cardiac surgery. This study was undertaken to compare the perioperative effects between isoflurane and fentanyl-midazolam-based anesthesia for heart transplantation. A retrospective cohort study was conducted by reviewing the medical records of heart transplantation in a single medical center from 1990 to 2013. Patients receiving isoflurane or fentanyl-midazolam-based anesthesia were included. Those with preoperative severe pulmonary, hepatic, or renal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…[22] Conflicting results have been reported regarding the effects of individual anesthetics used in GA on perioperative and postoperative glycemia. Some authors have shown better glycemic control with isoflurane compared to TIVA with midazolam in cardiac surgery, [23] while other studies did not find significant differences between TIVA with midazolam and balanced anesthesia, [24] or between TIVA with propofol or midazolam. [25] Our study did not find significant glycemic differences between the study groups.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Conflicting results have been reported regarding the effects of individual anesthetics used in GA on perioperative and postoperative glycemia. Some authors have shown better glycemic control with isoflurane compared to TIVA with midazolam in cardiac surgery, [23] while other studies did not find significant differences between TIVA with midazolam and balanced anesthesia, [24] or between TIVA with propofol or midazolam. [25] Our study did not find significant glycemic differences between the study groups.…”
Section: Discussionmentioning
confidence: 99%
“…Patients receiving normothermic CPB according to the surgeon's decision during operation were also excluded. Before the commencement of this study, statistical power analyses performed with G*Power [13] revealed that a sample size of 27 patients per group was required to achieve 80% power for an effect size of 0.78 in the primary endpoint of post-CPB blood glucose levels [14] because we did not find any previously published data on lactate levels following nitroglycerin infusion during rewarming of CPB. A total of 80 patients were enrolled to allow for patient dropout.…”
Section: Participantsmentioning
confidence: 99%
“…However, its dosedependent vasodilatory effects on cerebral oxygenation, heparin reversal, and metabolic homeostasis, such as blood glucose and lactate levels, were scarcely reported in previous studies when we commenced this prospective study. Therefore, the significantly different glucose levels in our previous study [14] were substituted for lactate levels as the primary endpoint of tissue perfusion for the calculation of the sample size. However, based on the present results from more than 30 patients in each group, we observed that most clinical variables were closely comparable.…”
Section: Limitationsmentioning
confidence: 99%
“…Fentanyl and sufentanil may pose hemodynamic effects by regulating the release of norepinephrine from the adrenal glands (Thomson, Hudson, Rosenbloom, & Torchia, ). Fentanyl significantly elevates the blood glucose level (Hsu et al, ) and heart rate, and on the other hand, dampens the cardiovascular response (Kirvela, Scheinin, & Lindgren, ). An adjuvant of fentanyl with midazolam and fluanisone has a direct effect on blood glucose, C‐lactate, and pyruvate (due to renal metabolism) and renal mean transit time, perhaps because of compromised renal function.…”
Section: Opioidsmentioning
confidence: 99%